PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PT POS INDONESIA (PERSERO) BEKASI - Parimita, Widya; Wahda, Laysa Aneu Afrilla; Handaru, Agung Wahyu (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
PENGARUH PENGEMBANGAN KARIR DAN MOTIVASITERHADAP KEPUASAN KERJAKARYAWAN PT POS INDONESIA (PERSERO) BEKASIWidya ParimitaFakultas Ekonomi Universitas Negeri JakartaEmail: widya_parimita@yahoo.comLaysa Aneu Afrilla WahdaFakultas Ekonomi Universitas Negeri JakartaEmail: laysaaneu@gmail.comAgung Wahyu HandaruFakultas Ekonomi Universitas Negeri JakartaEmail: agung_1178@yahoo.comABSTRACTThe purpose of this study were: 1) to know the overview of career development,motivation, and job satisfaction the employee at PT Pos Indonesia (Persero)Bekasi. 2) To know the influence of career development on job satisfaction. 3) Toknow the influence of motivation on job satisfaction. 4) To know the influence ofcareer development and motivation simultaneously on job satisfaction. Researchcarried out by the simple random sampling method on 154 employees at PT. PosIndonesia (Persero) Bekasi as respondents, while the technique of data collectionis done by distributing questionnaires, which is processed using SPSS 21.0. Theresearch using descriptive and explanatory. The results of the regression indicatethat there is influence career development towards job satisfaction and there isinfluence between motivatiom towards job satisfaction. Career development andmotivation simultaneously influence the job satisfaction and significance. Thisresearch has figured out the score of career development and motivation on worksatisfaction while the rest is influenced by the other factors.Keywords: Career Development, Motivation, Job Satisfaction